Measuring Voluntary Control Over Hallucinations: The Yale Control Over Perceptual Experiences (COPE) Scales. (28th January 2022) - Mourgues, Catalina; Hammer, Allison; Fisher, Victoria; Kafadar, Eren; Quagan, Brittany; Bien, Claire; Jaeger, Hale; Thomas, Rigi; Sibarium, Ely; Negreira, Alyson M; Sarisik, Elif; Polisetty, Vasishta; et al.
Abstract: Auditory verbal hallucinations (AVH) frequently cause significant distress and dysfunction, and may be unresponsive to conventional treatments. Some voice-hearers report an ability to fully control the onset and offset of their AVH, making them significantly less disruptive. Measuring and understanding these abilities may lead to novel interventions to enhance control over AVH. Fifty-two voice-hearers participated in the pilot study. 318 participants with frequent AVH participated in the validation study. A pool of 59 items was developed by a diverse team including voice-hearers and clinicians. After the pilot study, 35 items were retained. Factorial structure was assessed with exploratory (EFA, n = 148) and confirmatory (CFA, n = 170) factor analyses. Reliability and convergent validity were assessed using a comprehensive battery of validated phenomenological and clinical scales. CFA on the final 18 items supported two factors for a Methods of Control Scale (5 items each, average ω = .87), and one factor for a Degree of Control Scale (8 items, average ω = .95). Correlation with clinical measures supported convergent validity. Degree of control was associated with positive clinical outcomes in voice-hearers both with and without a psychosis-spectrum diagnosis. Degree of control also varied with quality of life independently of symptom severity and AVH content. The Yale control over perceptual experiences (COPE) Scales robustly measure voice-hearers' control over AVH and exhibit sound psychometric properties. Results demonstrate that the capacity to voluntarily control AVH is independently associated with positive clinical outcomes. Reliable measurement of control over AVH will enable future development of interventions meant to bolster that control.